Siklus Hidup Ulat Sutera Samia ricini Daun Singkong dan Potensi Pakan dari Agroforestri Sengon dan Singkong di Widodomartani, Ngemplak, Sleman, Daerah Istimewa Yogyakarta - Prijono, Agus; Rawana; Woesono, Hastanto Bowo; Nugroho, Yunianto Hargo (Fakultas Kehutanan Institut Pertanian STIPER Yogyakarta, 2024)
The people of Widodomartani mostly have agricultural land that is managed independently. One of the agricultural land management practices carried out is sengon and cassava agroforestry. Cassava in addition to being taken from the tubers and leaves for vegetables can also be used for the cultivation of samia ricini silkworms. Cassava is usually planted on the sengon path on the guludan path. The planting distance of sengon is 2m x 2m while the distance between yams is 2m x 0.7 m or between sengon there are 3 cassava. This study aims to determine life cycle of Samia ricini silkworms, the production of cassava leaves and their potential for the cultivation of Samia ricini silkworms. The method used was to take samples of cassava plants to calculate the number of stalks, calculate the weight of the leaves and convert the feed needs of Samia ricini caterpillars and to known life cycle of Samia ricini silkworms. The results of the study obtained for life cycle of Samia ricini silkworms 53-61 days (eeg fases 7 days, 21-30 days caterpillars/larva, 17 days cocoon/pupae, and 8 days imago/silkworms) and an average leaf production per cassava plant of 123,466 leaf stalks. The number of plants per ha is around 7,142,857 plants. The potential production of the number of thigh leaves is 881,899,982 stalks. The average weight of 1 petiole is 4.06 grams (average 2.786 grams without stalk). The feed requirement of 1 large caterpillar is 15.3097 petioles / 62.157 gr (42.6528 gr without stalk). One hectare of sengon and cassava agroforestry land can support the cultivation of 57,603,348 samia ricini caterpillars. The average weight of one cocoon is 2.10 grams and silk (cocoon not pupae) 0.28571 gr (13,6%). One ha of land can support the production of silk cocoon as much as 120,967,030 gr or 120,967 kg.